The effect of fibres on steel bar corrosion and flexural behaviour of corroded RC beams. (15th May 2018) - Berrocal, Carlos G.; Löfgren, Ingemar; Lundgren, Karin
Highlights: Fibre reinforcement reduced corrosion in terms of total rebar weight loss. The addition of fibres changed the corrosion pattern of reinforcing bars in concrete. Fibres positively affected the load capacity but not the rotation capacity. The rotation capacity of the beams was severely reduced by corrosion of reinforcement. Abstract: This paper reports the results of an experimental programme aimed at investigating the influence of fibre reinforcement on the corrosion process of conventional steel rebar embedded in cracked concrete and on the flexural behaviour of reinforced concrete beams. Un- and pre-cracked reinforced concrete beams were subjected to natural corrosion through cyclic exposure to a 10% chloride solution for a period of three years. Subsequently, flexural tests were carried out under three-point bending configuration. Gravimetric measurements showed higher corrosion levels for bars in plain concrete compared to fibre reinforced concrete, and visual inspection of the bars revealed that fibres promoted a more distributed corrosion pattern. From detailed examination of the bars through 3D laser scanning technique, the main parameter controlling the local corrosion level of individual pits appears to be the local interfacial conditions; grater loads during pre-cracking and repeated load cycles yielded greater cross-sectional losses. Moreover, there was a tendency for more localized corrosion in beams with open cracks, indicating a possible impact of crack width on the extension of corrosion. The results from the flexural tests showed a consistent increase of load capacity for fibre reinforced beams compared to their plain concrete counterparts but only a marginal influence of the fibres on the rotation capacity. Furthermore, the rotation capacity of the beams was found to decrease several times faster than the load capacity with increasing loss of rebar cross-sectional area.